2002
DOI: 10.1100/tsw.2002.91
|View full text |Cite
|
Sign up to set email alerts
|

Bioremediation of Heavy Metals and Organic Toxicants by Composting

Abstract: Hazardous organic and metallic residues or by-products can enter into plants, soils, and sediments from processes associated with domestic, municipal, agricultural, industrial, and military activities. Handling, ingestion, application to land or other distributions of the contaminated materials into the environment might render harm to humans, livestock, wildlife, crops, or native plants. Considerable remediation of the hazardous wastes or contaminated plants, soils, and sediments can be accomplished by compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(44 citation statements)
references
References 115 publications
2
42
0
Order By: Relevance
“…Rev Environ Sci Biotechnol (2010) 9:215-288 245 bioremediation technique for degrading toxic organic compounds and perhaps lowering their persistence and toxicity in organic residues and wastes (Barker and Bryson 2002). The biochemical and physicochemical processes of remediation in composts are similar to those that usually occur biologically in soil.…”
Section: Eisenia Fetidamentioning
confidence: 98%
“…Rev Environ Sci Biotechnol (2010) 9:215-288 245 bioremediation technique for degrading toxic organic compounds and perhaps lowering their persistence and toxicity in organic residues and wastes (Barker and Bryson 2002). The biochemical and physicochemical processes of remediation in composts are similar to those that usually occur biologically in soil.…”
Section: Eisenia Fetidamentioning
confidence: 98%
“…CO 2 effect on climate change) have led to strategies oriented towards sustainability, as the Directive 2009/08/EC, which established legally binding targets within the European Union (EU) for 2020 in order to reach a 20% share of renewable energy on the final energy consumption. Within the renewable en-2 which reduces heavy metal availability and diminish the presence of plant pathogens and organic toxicants (Barker & Bryson, 2002;Noble & Roberts, 2004). As observed for SS, when sewage sludge compost (SSC) is applied to the soil, fertility and plant growth are enhanced (Casado-Vela et al, 2006;Larchevêque et al, 2006;Song & Ju Lee, 2010).…”
Section: Introductionmentioning
confidence: 96%
“…Pre-exposure to 2,4-D and MCPA has been reported to boost degrading populations, thereby increasing the dissipation of these herbicides in agricultural soils (Baelum et al 2008;Smith and Aubin 1991). Differences in dissipation between both MCPA levels underline the importance of initial herbicide concentrations in Several studies have shown that degradation of organic compounds in soils can be improved by adding raw organic matter or compost (e.g., Barker and Bryson 2002;López-Piñeiro et al 2013). In our study, litter addition significantly accelerated MCPA dissipation only in soils exposed to the high MCPA concentration ( Fig.…”
Section: Discussionmentioning
confidence: 97%